2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2453
|View full text |Cite
|
Sign up to set email alerts
|

Digestible arginine concentrations in the diet of Japanese quails

Abstract: The objective of this study was to evaluate the effect of different levels of arginine in the diet of Japanese quails and to determine which provides the best egg production indices. We used 400 birds with an initial average weight of 180 g at 140 days of age. These were distributed among experimental units in a randomized design. Five levels of digestible arginine were studied (1.148, 1.256, 1.364, 1.472, and 1.580%) in reference to a fixed level of digestible lysine (1.083%; for arginine to lysine ratios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 6 publications
(13 reference statements)
2
15
3
Order By: Relevance
“…In the current study, it was observed that increasing Arg:Lys ratios did not compromise the performance or egg quality traits of Japanese quails. However, contrary to our findings, Maurício et al (2016) observed a linear decrease egg production when Japanese quails were fed SID Arg:Lys ratios ranging from 106 to 146%, showing detrimental effects of excessive Arg supply on the performance, and that a 106% SID Arg:Lys ratio warrants proper quail performance.…”
Section: Optimal Standardized Ileal Digestible Arginine To Lysine Ratcontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study, it was observed that increasing Arg:Lys ratios did not compromise the performance or egg quality traits of Japanese quails. However, contrary to our findings, Maurício et al (2016) observed a linear decrease egg production when Japanese quails were fed SID Arg:Lys ratios ranging from 106 to 146%, showing detrimental effects of excessive Arg supply on the performance, and that a 106% SID Arg:Lys ratio warrants proper quail performance.…”
Section: Optimal Standardized Ileal Digestible Arginine To Lysine Ratcontrasting
confidence: 99%
“…Although such nutritional recommendations are important references, further studies are needed to update the nutritional requirements of Japanese quails. Reis et al, 2012 andMaurício et al, 2016 demonstrated that the optimal SID Arg:Lys ratios for Japanese quails are lower than the recommendations mentioned above. Therefore, this study was conducted to determine the optimal SID (standardized ileal digestible) Arg:Lys ratio for Japanese quails in the egglaying phase.…”
Section: Introductionmentioning
confidence: 89%
“…Eight studies were found on the arginine requirement for Japanese quails in laying phase ( Reis et al., 2012 ; Cavalcante, 2013 ; Santos, 2013 ; Silva, 2014 ; Bülbül et al., 2015 ; Maurício et al., 2016 ; Maurício et al., 2018 ; Tuesta et al., 2018 ) and the arginine requirement ranged from 0.945% to 1.472% or 253 to 377 mg/ bird per day. On the one hand, Ball et al.…”
Section: Introductionmentioning
confidence: 99%
“…[45] evaluated diferent levels of digestible arginine in the diet of Japanese quails, with diets formulated by the supplementation technique, estimated an ideal dietary arginine level of 1.148% in diets with 1.083% digestible lysine and relation arginine/lysine of 1.06.…”
Section: Amino Acids Methodologies: Techniques For Preparing Dietsmentioning
confidence: 99%
“…The supplementation technique is widely used [38][39][40][41][42][43][44][45] and has generated a large number of discrepant nutritional information. The main factor is the imbalance between amino acids.…”
Section: Amino Acids Methodologies: Techniques For Preparing Dietsmentioning
confidence: 99%